One more time with feeling: a rejoinder to Clair’s and Wood’s responses - Alberts, Jess K.; Riforgiate, Sarah E.; Tracy, Sarah; Trethewey, Angela (My University, 2011)
In this rejoinder, we respond to the following claims regarding our integrated theory of domestic labor found in the commentaries by Julia T. Wood and Robin Patric Clair (2011, this issue): that we are establishing a ruler for the division of domestic; that our theory is biased toward the over-performer's rule or standard; that disagreements over domestic labor are primarily narrative constructions; and that our theory suggests a less than sanguine view of the potential for change in how men and women are socialized regarding the performance of domestic labor. In so doing, we argue that what Julia T. Wood describes as a “ruler” is not ours to create but rather is specific to each dyad and typically established by the partner with the lowest threshold level, be it a woman or a man. We also maintain that while a narrative approach provides a way to understand couples' interpretations of their experience, we believe a distinct value of our integrative theory is in helping to explain behavior and offer redress where such is needed. Finally, we argue that although our perspective regarding change may seem less than sanguine, that simply waiting for change to occur is of little benefit to those individuals and marriages/relationships suffering from lack of change in the here and now.
One more time with feeling: a rejoinder to Wood’s and Clair’s commentaries
Keywords: Domestic labor; Division of domestic labor; Sex roles